(untitled) (Harmoni, 2014)
Karimun Regency is located in the periphery of Indonesia, located on the shores and bordering international shipping lanes. As a territory on the border, Karimun is a strategic area. Its strategic position means that Karimun is plagued with a number of issues, including religious ones. This qualitative study describes the development of religious service by the local offices of the Ministry of Religious AffairsΓÇöboth its successes and its limits. This study suggests that there are ΓÇ£gapsΓÇ¥ in the organizational structure between the Ministry of Religious Affairs in Jakarta with the local offices. This study argues that discrimination in the carrying out of religious service occurs. It is the leadership that has the capacity to deal with the deficiencies in organizational structure. It needs to address this issue; if not, the disharmony amongst interreligious groups in Karimun will continue.